Bulgaria Detailed Assessment of Observance : Basel Core Principles for Effective Banking Supervision - International Monetary Fund; World Bank (Washington, DC, 2015)
This assessment of the current state of the implementation of the Basel core principles (BCP) for effective banking supervision in Bulgaria has been completed as a stand-alone report on the observance of standards and codes undertaken by the international monetary fund (IMF) and the World Bank during March of 2015 at the request of the Bulgarian authorities. It reflects the regulatory and supervisory framework in place as of the date of the completion of the assessment. The Bulgarian National Bank (BNB) has an internal governance structure which, by vesting the majority of the powers of supervision in the Deputy Governor for banking supervision, exposes the supervisory function to risks. Under the BNB’s legal structure, supervision and enforcement is dissociated from the Governing Council, and the Governing Council has no right to compel transparency of decision making or to impose a framework to ensure consistency in the use of the enforcement regime. There are material concerns that the BNB is too resource constrained to deliver effective minimum levels of supervision. Despite a broad range of supervisory powers, there are some gaps in the legal framework that unduly restrict the BNB’s locus. The BNB has a good understanding of risk and many strong practices, and also making good use of international standards and guidelines, but there are some important system wide vulnerabilities. The assessment team reviewed the framework of laws, rules, and guidance and held extensive meetings with officials of the BNB, and additional meetings with the Finance Ministry, auditing firms, professional bodies, and banking sector participants. The authorities provided a comprehensive self-assessment of the CPs, as well as detailed responses to additional questionnaires, and facilitated access to supervisory documents and files on a confidential basis as well as staff and systems.